Health-care access dimensions and ovarian cancer survival: SEER-Medicare analysis of the ORCHiD study. Issue 2 (16th February 2023) - Montes de Oca, Mary Katherine; Chen, Quan; Howell, Elizabeth; Wilson, Lauren E; Meernik, Clare; Previs, Rebecca A; Huang, Bin; Pisu, Maria; Liang, Margaret I; Ward, Kevin C; Schymura, Maria J; Berchuck, Andrew; et al.
Abstract: Background: Racial and ethnic disparities in ovarian cancer (OC) survival are well-documented. However, few studies have investigated how health-care access (HCA) contributes to these disparities. Methods: To evaluate the influence of HCA on OC mortality, we analyzed 2008-2015 Surveillance, Epidemiology, and End Results-Medicare data. Multivariable Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the association between HCA dimensions (affordability, availability, accessibility) and OC-specific and all-cause mortality, adjusting for patient characteristics and treatment receipt. Results: The study cohort included 7590 OC patients: 454 (6.0%) Hispanic, 501 (6.6%) Non-Hispanic (NH) Black, and 6635 (87.4%) NH White. Higher affordability (HR = 0.90, 95% CI = 0.87 to 0.94), availability (HR = 0.95, 95% CI = 0.92 to 0.99), and accessibility scores (HR = 0.93, 95% CI = 0.87 to 0.99) were associated with lower risk of OC mortality after adjusting for demographic and clinical factors. Racial disparities were observed after additional adjustment for these HCA dimensions: NH Black patients experienced a 26% higher risk of OC mortality compared with NH White patients (HR = 1.26, 95% CI = 1.11 to 1.43) and a 45% higher risk among patients who survived at least 12 months (HR = 1.45, 95% CI = 1.16 to 1.81). Conclusions: HCA dimensions are statistically significantly associated with mortality after OC and explain some, but not all, of the observed racial disparity in survival of patients with OC. Although equalizing access to quality health care remains critical, research on other HCA dimensions is needed to determine additional factors contributing to disparate OC outcomes by race and ethnicity and advance the field toward health equity.